Synergistic Antimicrobial Activity of Biogenic Silver Nanoparticles and Acanthospermum australe Essential Oil against Skin Infection Pathogens - Mussin, Javier Esteban (2024)
In response to the steady increase in antimicrobial-resistant strains, the World Health Organisation has emphasised the need to investigate new antimicrobial agents and alternative therapies that improve the spectrum of activity and reduce the dose required, thus improving safety. This study focused on the characterisation of Acanthospermum australe essential oil and green-synthesis silver nanoparticles (AgNP), evaluating their cytotoxicity in human cells, antimicrobial activity and synergistic effect against pathogens causing skin infections. The main components of the essential oil were germacrene A (24.07%), γ-cadinene (21.47%) and trans-caryophyllene (14.97%). Spherical AgNP with a diameter of 15 ± 3 nm were synthesised. The essential oil showed antimicrobial activity against dermatophytes and Malassezia globosa, while AgNP were found to be active against bacteria, yeasts and dermatophytes. Both compounds were found to be primarily non-cytotoxic at the concentrations required to inhibit microbial growth. Furthermore, the combined use of essential oil and AgNP showed a synergistic antimicrobial effect against dermatophytes and M. globosa. In conclusion, the results suggest that the combined use of bioactive compounds from natural sources, such as essential oil and biogenic AgNP, has the potential to improve antimicrobial efficacy against specific skin pathogens, particularly Microsporum canis, Nannizzia gypsea and M. globosa.